KESIAPAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN MODUL AJAR PADA KURIKULUM MERDEKA DI SMPN 03 PANCUNG SOAL - Olivia, Olivia; Nurhapipah, Nurhapipah; Pohan, Abdul Hakim; Nelwati, Sasmi; Misra, Misra (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
Indonesia is currently implementing a new curriculum known as the Merdeka Curriculum, which requires all educational institutions to prepare themselves to implement the curriculum, as well as at SMPN 03 Pancung Soal, Pesisir Selatan Regency. The objectives of this study are: 1) Knowing the teacher's understanding of the independent curriculum, 2) Knowing the readiness of teachers in preparing teaching modules, 3) Knowing solutions for teachers in developing teaching modules. The research method was carried out by descriptive analysis with qualitative research type with data collection by interviewing Islamic religious education teachers and document studies based on literature review. The results of this study show that the readiness of Islamic Religious Education teachers in preparing teaching modules on the independent curriculum at SMPN 03 Pancung Soal is still not optimal, due to the lack of guidance and training such as attending seminars related to this. In this case, the teacher is required to be able to compile teaching modules by analyzing conditions according to the needs of teachers and students based on background, then must pay attention to the facilities and infrastructure available at school, through the ability and creativity of the teacher. With guidance in the preparation of teaching modules, teachers will easily develop teaching modules according to the criteria of student